Effect of tDCS targeting the dorsolateral prefrontal cortex on psychophysiological responses and brain oxygenation during exercise in healthy adults: a proof-of-concept randomized controlled trial - Machado, Daniel Gomes da Silva; Melo, Mercia Jaynne Leandro de; Mendonça, Matheus Alves; Leiros, Daniel de Medeiros; Borges da Silva, Everton; Forti, Rodrigo Menezes; Mesquita, Rickson C.; Faro, Heloiana; Acevedo, Edmund O. (Frontiers in Physiology, 2025)
BackgroundPhysical inactivity is a major public health challenge, and strategies to improve exercise adherence are crucial. Affective responses play a key role in exercise behavior, and transcranial direct current stimulation (tDCS), a non-invasive technique that applies low-intensity current to the scalp, may modulate these responses. However, evidence supporting its effectiveness remains equivocal.ObjectiveThis study aimed to evaluate the effects of tDCS targeting the dorsolateral prefrontal cortex (DLPFC) on psychophysiological responses and brain oxygenation in healthy adults.MethodsParticipants first completed a maximal incremental exercise test to assess exercise performance and aerobic fitness. In two subsequent sessions, participants received either active tDCS over the DLPFC or sham stimulation for 20 min, followed by a 20-min vigorous-intensity exercise session. Heart rate (HR) and brain oxygenation (measured via functional near-infrared spectroscopy, fNIRS) were continuously monitored during exercise. Affective valence, arousal, and rating of perceived exertion (RPE) were self-reported every 5 min. Data were analyzed using Generalized Estimating Equations and Generalized Mixed Models, with significance set at p < 0.05.ResultsBrain oxygenation increased after exercise compared to baseline and post-tDCS (p < 0.05). However, tDCS did not significantly alter brain oxygenation at rest (p > 0.3) or during exercise (p > 0.09). No significant effect of tDCS was observed for the affective responses (p > 0.08), arousal (p > 0.85), or RPE (leg: p > 0.90; whole-body: p > 0.28).ConclusionDLPFC-targeted tDCS does not modulate brain oxygenation or enhance psychophysiological responses during vigorous-intensity exercise in healthy individuals. Future studies should explore exercise preference and tolerance, and the effects of tDCS on clinical populations.